Correlation of Nutritional Status and Subjective Fatigue with the Productivity of Labourers - Hendra Purbaya; Indriati Paskarini (Universitas Airlangga, 2020)
Introduction: The scallions sorting and weighing center are an informal sector business engaged in fulfilling the supply of scallions for the wholesale market in Sidoarjo. The labourers at the sorting and weighing scallions have varying nutritional status. The labourers with the normal nutritional status of produce more of processed scallions, whereas those who have poor nutritional status usually the produce fewer number of processed scallions. Work fatigue in the labourers also determines their productivity. Therefore, this study aims to analyze the correlation between individual characteristics, nutritional status, subjective fatigue and the productivity of the labourers in the sorting and weighing scallions. Methods: Based on the objectives of this study, this research is an observational and correlational type of research. The samples of this study were 28 labourers. The variables of this study are individual characteristics, nutritional status, subjective fatigue, and work productivity. Results: The magnitude of the value of the contingency coefficient test and the Spearman correlation with the value α = 1% which showed the results of relationship between years of service with productivity, nutritional status with productivity and also subjective fatigue with productivity. The sig value of correlation coefficient is less than 0.01. Conclusion: There is a relationship between individual characteristics, nutritional status, subjective fatigue with work productivity in the sorting and weighing scallions.Keywords: education, fatigue, nutritional status, productivity, time of services